ANALISIS FAKTOR YANG MEMPENGARUHI KEMAUAN BAYAR PENGHUNI RUSUNAWA - Putri, Faradiah Hildy; Iqbal, Maulid M.; Juliantina, Ika (CANTILEVER, 2018)
Rental income of Kasnariansyah rent flats can not cover the increase in operating costs so that the new rental rates are adjusted. Adjustment of rental price is limited to 1/3 of the residents income. The purpose of this study is 1) determine the amount of Willingness to Pay (WTP), 2) determine the amount of Ability to Pay (ATP) 3) determine variables that influence the willingness to pay the occupants. The results showed that ATP and WTP approached the value of new rental rates. Factor of willingness to pay is influenced by income and perception of facility.